Pendidikan dan Penelitian Kehutanan di Berbagai Belahan Dunia: Sebuah Tinjauan Literatur - Iwan Maryawan; Auliana Rochsas (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
This paper compiles research from various journals on forestry education and forestry research from various countries on different continents. The method used is a literature review by finding, analyzing, classifying, and concluding data from various accredited national and international journals indexed by Scopus and other references that support the locus of forestry education and training in native and artificial forests. The approach of each country in conducting forestry education and forestry research is adjusted to the policy, climate and budget availability. The challenges and management strategies carried out are also adapted to human resources, natural resources, educational curricula and the availability of budgets and policies of each country. The education curriculum is part of the challenge that is of particular concern because education plays a role in changing the citizen's paradigm of forest management.